Motor Incoordination in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The relationship between motor performance, attention deficit, impulsiveness, and hyperactivity in 42 school-aged children with ADHD (36 males, 6 females; mean age 8 years 2 months; range 6-11 years) was studied at National Taiwan University, Taipei, Taiwan.